The Training for Triharjo Village’s Stockbreeders on Production of BSF Larve’s Oil as Potential Cosmetic Raw Material - Suryaneta; Kiki Yuli Handayani; Achmad Gus Fahmi; Tikarahayu Putri; Indah Puspita Sari; Iwan Syahjoko Saputra (Asian Journal of Community Services, 2022)
Indonesia has seen a rise in Black Soldier Fly maggots. Maggot farming offers great economic diversification. BSF (maggot) larvae may eat many organic materials, making them special. This helps bioconvert organic waste, which can damage the environment and harm people's health if not treated properly. Protein-rich maggots are animal feed ingredients. Serious maggot cultivation can create new jobs. This maggot culture has a hidden gem that must be removed. Maggot oil studies still produce animal feed. Maggot oil is antibacterial and emollient, making it a cosmetic and medicinal ingredient, according to worldwide studies. Cosmetics use fats as viscosity enhancers or emulsifiers. As a proof of concept, BSF larvae fat will be used in hand cream compositions to show its potential in organic waste processing, animal feed, and health and beauty additives. Naturally, national and international scientific journals and social media have not broadly shared this information and talents. The Cosmetic Engineering study program's Community Service Team shares information, insights, and talents to connect research, education, and community applications. The ITERA Cosmetics Engineering team will train maggot breeders in Triharjo village to increase maggot production and diversify maggot products to boost sales.